Digital media guidelines for sustainable tourism: A case study of historical tourism in Baan Khamkerm-Nong Saeng, Nakhon Phanom province, Thailand - Boonprachoom, Supatcharee; Sirirat, Preedaree; Manorom, Arnunnit (Humanities, Arts and Social Sciences Studies, 2025)
This study aims to develop digital media prototypes to promote historical tourism in the Baan Khamkerm-Nong Saeng community of Nakhon Phanom province, Thailand. It focuses specifically on Saint Joseph’s Church, the oldest remaining church in the upper northeastern region of Thailand, which has the potential to be developed as a historical tourist attraction. However, maintaining its tourist attractions’ history and values proves challenging because of the community’s limitations in identity communication and public relations. The study applied a participatory action research approach, collecting data from community leaders, history and culture experts, tour operators, media and production designers, and Thai tourists through focus groups, observations, and reflections. Data were analysed and developed into images, video clips, infographic, and text presented on Facebook, which were used to convey identity and historical values. The results showed that historical value, physical potential, and activities can promote historical tourism using digital media. Designing digital media based on the community’s participation that reflects the historical tourist attractions’ potential can contribute to the United Nation’s Sustainable Development Goals, especially in fostering inclusive economic growth, cultural preservation, and sustainable communities. Incorporating cognitive response theory, audience perceptions, and message evaluations were considered throughout content development. However, to ensure sustainability, historical tourism and media development, it must be passed on to future generations via continuous learning, local capacity building and youth engagement.